2013
DOI: 10.3201/eid1909.130117
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Diphtheritic Polyneuropathy by Acute Flaccid Paralysis Surveillance, India

Abstract: Diphtheritic polyneuropathy is a vaccine-preventable illness caused by exotoxin-producing strains of Corynebacterium diphtheriae. We present a retrospective convenience case series of 15 children (6 girls) <15 years of age (mean age 5.2 years, case-fatality rate 53%, and 1 additional case-patient who was ventilator dependent at the time of last follow-up; median follow-up period 60 days) with signs and symptoms suggestive of diphtheritic polyneuropathy. All cases were identified through national acute flaccid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…9 Mateen et al found palatal palsy only in 13% cases. 10 The onset of neurological complications in our series was seen from 6-51 days after respiratory symptoms. Similarly, in the Latvian study of 50 adult patients with diphtheritic paralysis, neurological complications appeared in 2-50 days (median, 10 days) after the onset of respiratory diphtheria.…”
Section: Discussionmentioning
confidence: 68%
“…9 Mateen et al found palatal palsy only in 13% cases. 10 The onset of neurological complications in our series was seen from 6-51 days after respiratory symptoms. Similarly, in the Latvian study of 50 adult patients with diphtheritic paralysis, neurological complications appeared in 2-50 days (median, 10 days) after the onset of respiratory diphtheria.…”
Section: Discussionmentioning
confidence: 68%
“…Causative role uncertain. PCR on fecal samples [ 30 ] Bacterial Diphtheria Africa, Central and South America, Asia, Europe Neurological toxicity from absorption and dissemination of diphtheria toxin Culture from throat and nose Need confirmation of toxin production [ 31 ] Lyme disease North America, Europe AFP is rare presentation Serological testing PCR on CSF [ 32 ] Botulism Worldwide Isolation of Clostridium botulinum from wound site Serum assay for botulinum toxin Electromyography [ 33 ] Rickettsia conorii Europe, Africa Cause of Mediterranean spotted fever. Rash very common.…”
Section: Discussionmentioning
confidence: 99%
“…DP is a common and potentially severe complication occurring in ∼20% of diphtheria patients, although recovery is possible 12. Dysphagia and dysphonia secondary to hypopharyngeal and palatal muscle weakness tend to have an onset in the order of days to weeks, with segmental demyelination of peripheral nerves resulting in limb weakness, loss of tendon reflexes and sensory disturbance developing weeks to months after the initial infection 13–16.…”
Section: Discussionmentioning
confidence: 99%